The Buddhist Education System for Moral and Spiritual Development in the Modern Society - Tri Saputra Medhācitto (Jurnal Budi Pekerti Agama Buddha, 2024)
This research aims to discover the application of Buddhist education system as revealed in the Buddhist scripture for moral and spiritual development in the modern society. This study is a type of qualitative research with library research approach. The data is collected from Buddhist scripture, especially Pali literature and contemporary works done by scholars such as journal, paper, books, etc. Most of education system in the modern society emphasizes on material profits but neglects the development of individual character. The Buddhist education system offers an effective solution for modern world to prevent the moral degradation. Buddhist education refers to the word “sikkhā” which means “good conduct or virtue,” highlighting that education is aimed not only for achieving the academic knowledge, but also training oneself in good conduct as the base of moral life. The Buddhist education system as revealed in the Buddhist scripture is able to contribute to moral and spiritual development in the society. Buddhist education highlights the development of oneself and others. Therefore, Buddhist education is aimed to produce generations who are beneficial for themselves and others (attahitāya ceva paṭipanno parahitāya ca).